A conflicting bifuzzy evaluation approach in multi-criteria decision making - Tarmudi, Zamali; Abdullah, Mohd Lazim; Md. Tap, Abu Osman (CESER, 2010)
The multi-criteria decision-making has received significant attention by both researchers and decision makers due to its ability to derive effectively a compromise solution in the decision process. The focus of this paper is to propose a conflicting bifuzzy evaluation in the overall decision process using linguistic expressions. The approach is based on the new theory sets, the so-called 'conflicting bifuzzy sets' (CBFS) which are an extension of Attanassov intutionistic fuzzy sets (IFS). A definition of the CBFS is discussed and the approach employs a multi-criteria decision making (MCDM) hybrid model which is developed using fuzzy analytic hierarchy process and fuzzy ideal solution. Through this proposed approach, the decision maker needs to evaluate all the qualitative criteria using totally linguistic expressions through both positive and negative aspects such as 'very good', 'good', 'slightly poor' etc. The direct assigned was employed to derive the importance weight of the criteria and the best compromise options among the potential alternatives was measured by the performance index.